Analysis of SOL-GEL Static Laser Light Scattering Data (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This paper is "Analysis of Static Laser Light Scattering Data of SOL-GEL". This method has the unique advantage of characterizing macromolecules in sol-gel experiments with a light source. The DLS method has the additional advantage that the signal-to-noise ratio (SNR) using sol-gel gZ(r) is less affected by the dust in the sample, unlike the SLS experiment where there is dust contamination. can cover the signal level to make an accurate estimate of the use of broken hard work. Analysis and solutions to this problem have not yet been developed. The results of the present study should be seen as a step in this direction.